2012
DOI: 10.1186/1752-1947-6-244
|View full text |Cite
|
Sign up to set email alerts
|

Delayed esophageal perforation following lightning strike: a case report and review of the literature

Abstract: IntroductionLightning is the second most common storm-related cause of death. The mortality following lightning strike is 10% to 30% and a large proportion of these people suffer cardiopulmonary arrest at the time of the strike. Much less commonly, solid organ injuries occur from either primary or secondary blunt force trauma.Case presentationTo the best of our knowledge, this is the first case report in the literature of an isolated esophageal rupture caused by lightning strike blunt force trauma.ConclusionsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[5] Bone fractures, brain hemorrhage and internal organ injuries can be revealed as a result of burst effect of lightning. [2,33] Bilateral or unilateral basal ganglia bleeding due to lightning strikes may also be seen. [7,34] In the postmortem study of Pincus et al, was reported cerebral edema, subarachnoid, subgaleal and periosteal hemorrhage may be seen due to lightning strikes.…”
Section: Brain Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Bone fractures, brain hemorrhage and internal organ injuries can be revealed as a result of burst effect of lightning. [2,33] Bilateral or unilateral basal ganglia bleeding due to lightning strikes may also be seen. [7,34] In the postmortem study of Pincus et al, was reported cerebral edema, subarachnoid, subgaleal and periosteal hemorrhage may be seen due to lightning strikes.…”
Section: Brain Effectsmentioning
confidence: 99%
“…[1] Lightning can emit more than 1 million volts of energy, thus more than 200,000 amperes of current may occur. [2] The air surrounding the lightning can heat up to 25,000 to 30,000 °C. However, it does not always cause serious injury, as lightning contact is very short (2 msec).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 0.2-1.7 deaths per million people are reportedly caused by lightning each year globally [ 2 ]. In India, lightning strikes are thought to be responsible for over 2500 fatalities every year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%